Application of Biomimetic Cell Membrane-Coated Nanocarriers in Cardiovascular Diseases - Zhao X; Chen W; Wu J; Shen Y; Xu B; Chen Z; Sun Y (International Journal of Nanomedicine, 2025)
Xufei Zhao,1,* Wu Chen,1,* Jiong Wu,1 Yan Shen,1 Bohui Xu,2 Zhen Chen,3 Yangyong Sun4 1Department of Pharmaceutics, School of Pharmacy, China Pharmaceutical University, Nanjing, Jiangsu, 210009, People’s Republic of China; 2School of Pharmacy, Nantong University, Nantong, 226019, People’s Republic of China; 3Department of Cardiology, Taixing People’s Hospital, Taixing, Jiangsu, 225400, People’s Republic of China; 4Department of Cardiothoracic Surgery, Affiliated People’s Hospital of Jiangsu University, Zhenjiang, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yangyong Sun; Zhen Chen, Email sunyangyong0116@163.com; zhench_cn@163.comAbstract: Biomimetic cell membrane-coated nanocarriers have gained attention as an innovative therapeutic strategy for cardiovascular diseases (CVDs) due to their capacity to mimic natural cellular architectures. This distinctive characteristic improves biocompatibility, enables evasion of immune surveillance, and promotes targeted drug delivery to specific disease sites. By harnessing cell membrane components from sources such as red blood cells, platelets, and immune cells, these nanocarriers can transport therapeutic agents directly to pathological areas, including atherosclerotic lesions, ischemic myocardial tissue, and injured vasculature. This review highlights recent progress in the development of cell membrane-coated nanocarriers for CVD treatment, focusing on their design, mechanisms of action, and preclinical therapeutic potential. Additionally, it examines key challenges to clinical application, including such as production scalability, structural stability, and regulatory challenges, while proposing strategies to overcome these limitations. The advancement of these biomimetic nanocarriers marks a promising direction in cardiovascular medicine, offering the possibility of more efficient and less invasive therapies for CVD patients. Keywords: biomimetic nanocarriers, cell membrane coating, cardiovascular disease, targeted drug delivery, immune evasion, preclinical studies, clinical translation, therapeutic nanotechnology